'I lost the faith in humanity.' Using William Golding's Lord of the Flies to explore ethical and moral issues through transnational, online literary exchange. Issue 2 (4th March 2022) - Naylor, Amanda; McGuinn, Nicholas; Shaikh, Ghazal; Varga, Zoltan; Rimmereide, Hege Emma
ABSTRACT: Researchers into Literature and Education from Norway, Pakistan and the United Kingdom used William Golding's Lord of the Flies to explore the potential of a literary text to encourage intercultural dialogue, employing an innovative teaching method, Google Circles, to provide a platform for asynchronous online discussion among three cohorts of students in higher education. The authors present here the ethical and moral responses to the novel. The authors' analysis of the data explores the students' thoughts about human nature and law and order, as well as responses made by the students to moral turning points in Golding's novel. The authors report that – although the novel provided a space for students from three national contexts to debate major existential questions using the affordances of the asynchronous digital platform – the students found it difficult to distinguish between the writer, the implied author and the narrative voice.